The effects of salt on coacervates formed by polyDADMAC and polyAA - Tay, Jordan Shih Liang (Nanyang Technological University, 2023)
The phenomenon of coacervation is driven by electrostatic interactions between oppositely charged poly-ions. The science of complex coacervate formation has been a topic of interest ever since its introduction led to breakthroughs in the materials science, biotechnology, and pharmaceutical sectors. Coacervate formation is affected by many factors such as polymer molecular weight and charge density, ionic strength, temperature, and pH. The study aimed to evaluate the influence of salt valency and pH on the formation of coacervates formed between positively charged polyDADMAC and negatively charged polyAA. To investigate the extent of coacervate formation, turbidity was selected as a key indicator, measured as a function of different salts and their concentrations. From the experimental results, polyAA/polyDADMAC mixing ratio of 1:1 and pH value of 9 were found to be most optimal for complex coacervation. The effects of different salt types and ions at varying concentrations on complex coacervates were studied, with reference to the critical salt concentration. In addition to taking cations and anions as variables, experiments were conducted on both monovalent and divalent salts to determine whether they have an enhancement or inhibitory effect on coacervates. The Hofmeister series also had a huge role to play in the research, by offering insights on the chaotropic or kosmotropic nature of ions. However, while the Hofmeister series can offer a general guide for predicting salt effects on complex coacervates, different polyelectrolyte systems and solution conditions result in specific effects that may oppose the Hofmeister trend. Therefore, this research allows for a more in-depth and systemic study on the impact of salt on complex coacervate by identifying new trends in relation to current complex coacervate experiments.